Emergy-Based Provincial Sustainability Dynamic Comparison in China - Lin, Longzhun; Liu, Gengyuan; Wang, Xueqi; Wang, Chen; Liu, Chang; Casazza, Marco (Journal of Environmental Accounting and Management, 2026)
In this paper, we account the emergy of 29 provinces in China in 2012 (excluding Tibet, Taiwan, Hong Kong, andMacao due to lack of data) based on the application of the NEAD accounting framework at the provincial level. Based on the emergy-related data of 29 provinces in 2007, the emergy indicators of 2007 and 2012 are compared and analyzed. This study selected ESR, ED, EIR, and ESI, which can comprehensively represent the indicators of a province’s economic, social, environmental, and sustainable development. At the same time, we also use Pearson correlation to analyze the correlation between the four indicators and the three most primitive economic and social indicators (AREA, POPULATION, GDP) to derive the internal driving factors of the province. Comparing the correlation coefficient in two years can lead to changes in the internal driving factors of the province. We draw the following conclusions: (1) From 2007 to 2012, the resources development in the western region is remarkable, and the central and eastern regions have made some efforts on sustainable development on the basis of the better economic development. However, there is still a long way to go before the economic and environmental conflicts are resolved. There is still a lot of effort to reach the level of comprehensive sustainable development. (2) The larger the area, the stronger the sustainable development capability, and from 2007 to 2012, this trend has weakened. The greater the GDP, the weaker the capacity for sustainable development, but from 2007 to 2012, this trend has weakened. There is no obvious correlation between population and economy, society and sustainable development.